Functional Convergence of Oxylipin and Abscisic Acid Pathways Controls Stomatal Closure in Response to Drought . Issue 3 (15th January 2014) - Savchenko, Tatyana; Kolla, Venkat A.; Wang, Chang-Quan; Nasafi, Zainab; Hicks, Derrick R.; Phadungchob, Bpantamars; Chehab, Wassim E.; Brandizzi, Federica; Froehlich, John; Dehesh, Katayoon
Abstract : Oxylipin affects stomatal closure, functioning most effectively with ABA in response to drought . Abstract: Membranes are primary sites of perception of environmental stimuli. Polyunsaturated fatty acids are major structural constituents of membranes that also function as modulators of a multitude of signal transduction pathways evoked by environmental stimuli. Different stresses induce production of a distinct blend of oxygenated polyunsaturated fatty acids, "oxylipins." We employed three Arabidopsis ( Arabidopsis thaliana ) ecotypes to examine the oxylipin signature in response to specific stresses and determined that wounding and drought differentially alter oxylipin profiles, particularly the allene oxide synthase branch of the oxylipin pathway, responsible for production of jasmonic acid (JA ) and its precursor 12-oxo-phytodienoic acid (12-OPDA ). Specifically, wounding induced both 12-OPDA and JA levels, whereas drought induced only the precursor 12-OPDA . Levels of the classical stress phytohormone abscisic acid (ABA ) were also mainly enhanced by drought and little by wounding. To explore the role of 12-OPDA in plant drought responses, we generated a range of transgenic lines and exploited the existing mutant plants that differ in their levels of stress-inducible 12-OPDA but display similar ABA levels. The plants producing higher 12-OPDA levels exhibited enhanced drought tolerance and reduced stomatal aperture. Furthermore, exogenously applied ABA and 12-OPDA, individually or combined, promote stomatal closure of ABA and allene oxide synthase biosynthetic mutants, albeit most effectively when combined. Using tomato ( Solanum lycopersicum ) and Brassica napus verified the potency of this combination in inducing stomatal closure in plants other than Arabidopsis. These data have identified drought as a stress signal that uncouples the conversion of 12-OPDA to JA and have revealed 12-OPDA as a drought-responsive regulator of stomatal closure functioning most effectively together with ABA .